Սահմանադրական սկզբունքների և նորմերի դերն ու նշանակությունը Եվրասիական տնտեսական միության միջպետական ինտեգրման գործընթացների շրջանակներում - Աբրահամ Աբրահամյան (ՀՀ ԳԱԱ հրատ.)
В статье автор обратился к исследованию основных проблем конституционных норм и принципов, роли и значения межгосударственных интеграционных процессов в рамках Евразийского экономического союза. Отмечая важность основных проблем интеграционных процессов государств – членов Евразийского экономического союза, а также результаты системного анализа конституционных норм, автор пришел к выводу, что конституционное право этих государств эффективно и адекватно регулирует межгосударственные взаимоотношения в рамках Евразийского экономического союза. In the article the author touches upon to the study of the basic problems of the constitutional norms and principles, the role and importance of interstate integration processes within the Eurasian Economic Union. Stressing the importance of the main problems of integration processes of states – members of the Eurasian Economic Union, as well as results of the system analysis of the constitutional norms, the author came to the conclusion that the constitutional law of these countries is to effectively and adequately regulate the interstate relations in the framework of the Eurasian Economic Union.
Keywords: International relations; Political Science; Law